1, 25-Dihydroxyvitamin D regulates macrophage activation through FBP1/PKR and ameliorates arthritis in TNF-transgenic mice. Issue 228 (April 2023) - Zhu, Wei; Zhu, Ye; Zhang, Shujun; Zhang, Weiting; Si, Zihou; Bai, Yuxi; Wu, Ying; Fu, Yao; Zhang, Yang; Zhang, Luyao; Zhang, Xiaomin; Zhu, Xiaodong
Abstract: 1, 25-Dihydroxyvitamin D (1, 25(OH)2 D3 ) has immunomodulatory activity and its deficiency correlates with rheumatoid arthritis (RA) incidence. Whether 1, 25(OH)2 D3 modulates macrophage activation or protects against RA remains unclear. We demonstrate that 1, 25(OH)2 D3 suppresses M1 macrophage polarization and CD80, IL-6, CXCL10, IFIT1, IFI44, and double-stranded RNA-dependent protein kinase R (PKR) expression in the macrophages of RA patients. In phorbol 12-myristate 13-acetate-induced THP-1 cells, 1, 25(OH)2 D3 upregulates fructose-1, 6-bisphosphatase 1 (FBP1) expression through direct promoter interaction. FBP1 interacts with PKR and promotes PKR ubiquitination degradation. SiR-FBP1 transfection impairs 1, 25(OH)2 D3 action and suppresses IL-6, CXCL10, IFIT1, IFI27, and IFI44 expression in macrophages, whereas siR-PKR transfection impairs siR-FBP1 activity in 1, 25(OH)2 D3 -treated macrophages. 1, 25(OH)2 D3 treatment ameliorates the clinical signs of arthritis in tumor necrosis factor-transgenic mice, inhibits M1 polarization and marker expression, and promotes FBP1 expression in mononuclear cells isolated from swollen joints; thus, 1, 25(OH)2 D3 suppresses M1 macrophage activation through FBP1/PKR and ameliorates arthritis by restoring the macrophage subtype. Highlights: 1, 25(OH)2 D3 modulates macrophage polarization and activation in RA patients. 1, 25(OH)2 D3 treatment ameliorates arthritis in TNF-Tg mice. FBP1 modulates 1, 25(OH)2 D3 -induced macrophage activity.